A FIBRILLAR INTERCELLULAR MATERIAL BETWEEN REAGGREGATING EMBRYONIC CHICK CELLS - Overton, Jane (The Rockefeller University Press, 1969)
Lanthanum staining of embryonic chick cell reaggregates reveals an intercellular material composed of fibrils. Fibrillar arrays may be composed of parallel fibrils with a 35 A center-to-center spacing. Fibrils may also be disoriented, long, and tortuous. Newly dissociated cells show little lanthanum staining surface material, but appreciable amounts are present after 6 hr of reaggregation. Examination of intact tissue does not give the same clear evidence of a fibrillar matrix surrounding the cells, but treatment with a number of agents permits observation of intercellular fibrils, and in some cases there is evidence of orientation. Thus fibrillar material must be taken into account in considering mechanisms of cell aggregation.